Association of sugar intake from different sources with incident depression in the prospective cohort of UK Biobank participants - Kaiser, Anna; Schaefer, Sylva M.; Behrendt, Inken; Eichner, Gerrit; Fasshauer, Mathias; Justus Liebig University Giessen (My University, 2023)
Purpose: To elucidate the association of different sources of free sugars (FS) and intrinsic sugars with depression risk in the prospective population-based UK Biobank cohort. Methods: Sugar consumption was assessed in 188,426 participants (age range: 39–72 years, 54.4% female) with at least one web-based dietary questionnaire (Oxford WebQ). The hazard ratios (HR) for incident depression were assessed with Cox proportional hazard regression models including sugar intake from different sources as penalized cubic splines to allow non-linear predictor effects. Over a mean follow-up of 12.3 (standard deviation 1.8) years, 5410 incident depression cases occurred. Results: FS intake was significantly associated with depression risk in an ascending approximately linear way with the lowest HR observed at 9% total energy (%E). In contrast, consumption of intrinsic sugars was not significantly related with incident depression. FS in beverages were significantly associated with depression risk in an ascending approximately linear way with the lowest HR at 4%E whereas no association was found for FS in solids. Concerning beverage types, FS in soda/fruit drinks, milk-based drinks, and tea/coffee were significantly and positively related to depression risk whereas the association was U-shaped for juice. Major findings were robust in sensitivity analyses. Conclusion: Only some sources of FS are positively associated with incident depression. Public health initiatives targeting FS subtypes might be most effective concerning depression risk if focused on the reduction of sugary beverages and more specifically soda/fruit drinks, milk-based drinks, and tea/coffee.
Keywords: Carbohydrates; Depression; Metabolic syndrome; Sugar; UK Biobank; ddc:360; ddc:360